A Comparative Analysis on the Effect of Poultry Manure and Pig Manure on Cabbage Yield Around Kabale University. - Amanya, Pride (Kabale University, 2024)
This study provided a comparative analysis of the effects of poultry manure and pig manure on cabbage yield in Kabale District. The primary goal was to optimize cabbage production to enhance the incomes of smallholder farmers, with three specific objectives: to evaluate the effects of poultry and pig manure on cabbage yields, to assess their impact on nutrient availability, and to examine their implications for soil microorganisms in cabbage fields. The study involved three treatments: poultry manure, pig manure, and a control group with no manure. Results revealed that poultry manure was the most effective treatment, achieving the highest average cabbage weight of 3.28 kg. This highlights poultry manure's potential as a highly effective organic fertilizer for cabbage cultivation. The pig manure treatment produced a moderate average cabbage weight of 2.86 kg, outperforming the control but falling short of poultry manure. The control group yielded the lowest average cabbage weight of 1.8 kg. The study also highlighted environmental considerations when choosing between poultry and pig manure. Poultry manure, with its higher nitrogen content, if not properly managed, poses risks of nitrogen runoff into nearby water bodies, leading to water pollution, algal blooms, and oxygen depletion, which can harm aquatic ecosystems. In conclusion, poultry manure's higher nitrogen levels contribute to improved vegetative growth and higher cabbage yields. However, its use requires careful management to mitigate potential environmental impacts. The study recommended that farmers in Kabale District adopt poultry manure to maximize cabbage yields. Additionally, agricultural extension services should provide training and demonstrations on the benefits and proper application of poultry manure to ensure sustainable farming practices.